Analisis Fenomena Money Politic Terhadap Daya Pilih Masyarakat Di Kelurahan Cempaka Permai Kota Bengkulu - Tiara Saputri; Anita Marianata (CV. ITTC INDONESIA, 2024)
ABSTRACT This research discusses the phenomenon of money politics in elections in Kelurahan Cempaka Permai, Bengkulu City, and its influence on people's voting power. Money politics has become a common practice that is accepted as a tradition in every general election. Many people see money politics as a form of seriousness from legislative candidates and an opportunity to gain economic benefits. This study uses qualitative methods with data collection techniques through interviews and observations to explore community perspectives. The results show that apathy towards elections, along with a lack of knowledge about candidates, means that most people are only motivated to participate when there is a monetary incentive. The practice of money politics increases participation, but based on economic motives, not political awareness. Using Alfred Schutz's phenomenological approach, this phenomenon is understood as people's response to the stimulus of money politics that has become entrenched in electoral culture. Therefore, anti-corruption education needs to be strengthened to make people aware of the negative impact of money politics, so as to break the cycle of this bad tradition in elections